How to increase COVID-19 vaccine uptake among children? determinants associated with vaccine compliance - Hoshen, Moshe; Shkalim Zemer, Vered; Ashkenazi, Shai; Grossman, Zachi; Gerstein, Maya; Yosef, Noga; Cohen, Moriya; Cohen, Herman Avner (Frontiers in Pediatrics, 2023)
Objective: To elucidate determinants associated with COVID-19 vaccine uptake in children and the association with parental vaccination. Methods: We performed a retrospective chart review of all children aged 5-11 years registered at a central district in Israel from November 21st, 2021 to April 30th, 2022, and characterized COVID-19 vaccinated versus unvaccinated individuals. Data retrieved from the electronic medical files included: demographics (age, gender, sector, socioeconomic status [SES]); COVID-19 vaccination (first and second doses) and influenza vaccination status; co-morbidities; and parental vaccinations for COVID-19. Results: Of the 61,776 children included in the study, 20,355 (32.9%) were vaccinated for COVID-19. The COVID-19 vaccination rate was similar amongst males and females and was higher in children aged 9-11 years compared to children aged 5-6 years. Multivariate analysis identified five independent determinants that were significantly (p<0.001) associated with low vaccination rates: Arab and ultra-orthodox sectors (odds ratios: 0.235 and 0.617, respectively); children aged 5-8 years; children of low SES; and children who had not received previous seasonal influenza vaccination. The highest uptake of two vaccine doses was among children with the following medical conditions: type 1 diabetes mellitus (84%), heart failure (83.3%), treatment with biological agents (75%), asthma (74.6%), and obesity (71.7%). Conclusion: This study highlights several pediatric sub-populations with low and high vaccine uptake. It is essential to focus on determinants associated with low vaccination rates.